Immunomodulatory Activity of Begonia Medicinalis Ethanolic Extract in Experimental Animals - Zubair, Muhammad Sulaiman; Syamsidi, Armini; Ihwan; Sulastri, Evi; Idris; Rahman, Arif; Widyasari, Novia; Pakaya, David (Indonesian Journal of Pharmacy, 2022)
Benalu batu (B. medicinalis) is a plant endemic to Central Sulawesi that has been reported to possess anticancer, antioxidant, and antiviral activities. The mechanism of action of these activities is still unclear. This study aimed to evaluate the immunostimulatory effect of ethanol extract of B. medicinalis on an in vivo model by measuring the macrophage phagocytotic activity and cytokine production of tumor necrosis factor-alpha (TNF-α) and interferon-gamma (IFN-γ) on male mice and rats, respectively. The extract was obtained by the maceration method for 3 × 24 h using 70% ethanol. The doses of the extract were 60, 120, and 240 mg/kg body weight (bw). The percentage of macrophage phagocytosis and the TNF-α, and IFN-γ levels were measured on the eighth day, one hour after intraperitoneal injection of Staphylococcus aureus ATCC 25923. The result showed that ethanol extract of B. medicinalis activated macrophage phagocytosis in a dose-dependent manner, with a significant increase in cytokine expression of TNF-α and IFN-γ. The optimal dose was 240 mg/kg bw, with a higher percentage of phagocytic activity and higher levels of TNF-α and IFN-γ than Stimuno® as a positive control and other dosage treatments. This study suggests that B. medicinalis ethanol extract has the effect of an immunomodulator and provides a scientific basis for traditional usage of this herb plant.